Kualifikasi Penentuan Kelulusan dan Analisis Penilaian Pendidikan Melalui Kemampuan Peserta Didik - Sani Susanti; Desy Natalia Manurung; Lio Je Cio Ginting; Mildani Ulfa Nazha; Romauli Siregar (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Graduate Competency Standards (SKL) and education evaluation criteria to determine student graduation. SKLs are the minimum standards that students must meet in order to be considered successful.The scope of SKLs covers the areas of knowledge, attitudes and skills according to the 2013 curriculum.Teacher factors, facilities and infrastructure affect the success of SKLs.The function of educational evaluation standards is to assess the ability of students based on the assessment carried out.The results of the assessment are used to develop learning.SKL performance is analyzed based on assessment results to determine student completeness.This article analyzes SKLs and educational evaluation criteria in determining school graduation.